Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 202340 by hardmath last updated on 24/Dec/23

Answered by MATHEMATICSAM last updated on 25/Dec/23

(1/( (√3) + (√2))) = (√3) − (√2)  (1/( (√4) + (√3))) = (√4) − (√3)  (1/( (√5) + (√4))) = (√5) − (√4)  .  .  .  .  (1/( (√(49)) + (√(48)))) = (√(49)) − (√(48))    (1/( (√3) + (√2))) + (1/( (√4) + (√3))) + (1/( (√5) + (√4))) + ... + (1/( (√(49)) + (√(48)))) + (√2)  = (√3) − (√2) + (√4) − (√3) + .... + (√(49)) − (√(48)) + (√2)  = (√(49)) = 7 (Ans)

$$\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}\:+\:\sqrt{\mathrm{2}}}\:=\:\sqrt{\mathrm{3}}\:−\:\sqrt{\mathrm{2}} \\ $$$$\frac{\mathrm{1}}{\:\sqrt{\mathrm{4}}\:+\:\sqrt{\mathrm{3}}}\:=\:\sqrt{\mathrm{4}}\:−\:\sqrt{\mathrm{3}} \\ $$$$\frac{\mathrm{1}}{\:\sqrt{\mathrm{5}}\:+\:\sqrt{\mathrm{4}}}\:=\:\sqrt{\mathrm{5}}\:−\:\sqrt{\mathrm{4}} \\ $$$$. \\ $$$$. \\ $$$$. \\ $$$$. \\ $$$$\frac{\mathrm{1}}{\:\sqrt{\mathrm{49}}\:+\:\sqrt{\mathrm{48}}}\:=\:\sqrt{\mathrm{49}}\:−\:\sqrt{\mathrm{48}} \\ $$$$ \\ $$$$\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}\:+\:\sqrt{\mathrm{2}}}\:+\:\frac{\mathrm{1}}{\:\sqrt{\mathrm{4}}\:+\:\sqrt{\mathrm{3}}}\:+\:\frac{\mathrm{1}}{\:\sqrt{\mathrm{5}}\:+\:\sqrt{\mathrm{4}}}\:+\:...\:+\:\frac{\mathrm{1}}{\:\sqrt{\mathrm{49}}\:+\:\sqrt{\mathrm{48}}}\:+\:\sqrt{\mathrm{2}} \\ $$$$=\:\cancel{\sqrt{\mathrm{3}}}\:−\:\cancel{\sqrt{\mathrm{2}}}\:+\:\cancel{\sqrt{\mathrm{4}}}\:−\:\cancel{\sqrt{\mathrm{3}}}\:+\:....\:+\:\sqrt{\mathrm{49}}\:−\:\cancel{\sqrt{\mathrm{48}}\:}+\:\cancel{\sqrt{\mathrm{2}}} \\ $$$$=\:\sqrt{\mathrm{49}}\:=\:\mathrm{7}\:\left(\mathrm{Ans}\right) \\ $$

Commented by hardmath last updated on 25/Dec/23

thankyou dear professors

$$\mathrm{thankyou}\:\mathrm{dear}\:\mathrm{professors} \\ $$

Answered by Frix last updated on 24/Dec/23

(1/( (√k)+(√(k−1))))=(√k)−(√(k−1))  Σ_(k=3) ^n  ((√k)−(√(k−1))) =(√n)−(√2)  ⇒ answer is (√(49))=7

$$\frac{\mathrm{1}}{\:\sqrt{{k}}+\sqrt{{k}−\mathrm{1}}}=\sqrt{{k}}−\sqrt{{k}−\mathrm{1}} \\ $$$$\underset{{k}=\mathrm{3}} {\overset{{n}} {\sum}}\:\left(\sqrt{{k}}−\sqrt{{k}−\mathrm{1}}\right)\:=\sqrt{{n}}−\sqrt{\mathrm{2}} \\ $$$$\Rightarrow\:\mathrm{answer}\:\mathrm{is}\:\sqrt{\mathrm{49}}=\mathrm{7} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com